Next generation transcriptomics and genomics elucidate biological complexity of microglia in health and disease. Issue 2 (4th June 2015) - Wes, Paul D.; Holtman, Inge R.; Boddeke, Erik W.G.M.; Möller, Thomas; Eggen, Bart J.L.
Abstract : Genome‐wide expression profiling technology has resulted in detailed transcriptome data for a wide range of tissues, conditions and diseases. In neuroscience, expression datasets were mostly generated using whole brain tissue samples, resulting in data from a mixture of cell types, including glial cells and neurons. Over the past few years, a rapidly increasing number of expression profiling studies using isolated microglial cell populations have been reported. In these studies, the microglia transcriptome was compared to other cell types, such as other brain cells and peripheral tissue macrophages, and related to aging and neurodegenerative conditions. A commonality found in many of these studies was that microglia possess distinct gene expression signatures. This repertoire of selectively‐expressed microglial genes highlight functions beyond immune responses, such as synaptic modulation and neurotrophic support, and open up avenues to explore as‐yet‐unexpected roles. These data provide improved understanding of disease pathology, and complement not only the aforementioned whole brain tissue transcriptome studies, but also genome‐ and epigenome‐wide association studies. In this review, insights obtained from isolated microglia transcriptome studies are presented, and compared to studies using other genome‐wide approaches. The relation of microglia to other tissue macrophages and glial cell populations, as well as the role of microglia in the aging brain and in neurodegenerative conditions, will be discussed. Many more of these types of studies are expected in the near future, hopefully leading to the identification of novel genes and targets for neurodegenerative conditions. GLIA 2016;64:197–213 Main Points: Microglia express a unique gene expression signature. Microglial phenotypes are altered during normal aging and in neurodegenerative disease. Microglial dysfunction is implicated in the etiology of Alzheimer's disease and Amyotrophic Lateral Sclerosis.